Sodium Thiosulfate in the Treatment of Calciphylaxis - Cohen, George F. (Matrix Medical Communications, 2013)
The authors review the presentation, diagnosis, and treatment of calciphylaxis and also describe applications of a novel therapeutic option, sodium thiosulfate. Two cases of advanced uremic calciphylaxis from both clinic and hospital settings are presented. One patient, a 57-year-old woman with end-stage renal disease, was treated with surgical debridement and sodium thiosulfate 25g three times a week. After introducing sodium thiosulfate treatment, the affected sites continue to heal with encouraging improvement of ulcer depth. Sodium thiosulfate was well-tolerated and facilitated wound healing. The patient did not develop sepsis. Sodium thiosulfate appears to be a viable first-line treatment for calciphylaxis and should be seriously considered early in the course of treatment.